Produksi Biodiesel dari Lipid Fitoplankton Nannochloropsis sp. Melalui Metode Ultrasonik - Raymond Kwangdinata; Indah Raya; Muhammad Zakir (Marina Chimica Acta, 2013)
A research on production of biodiesel from lipid of phytoplankton Nannochloropsis sp. through ultrasonic extraction method has been done. In this research, we carried out a series of phytoplankton culture to determine the optimum time of growth and biodiesel synthesis process from phytoplankton lipids. Process of biodiesel synthesis consists of two steps, i.e isolation of phytoplankton lipids and biodiesel synthesis from  that  lipids.  Oil  isolation  process  was  carried  out  by  ultrasonic  extraction method using ethanol 96 % while biodiesel synthesis was carried out by transesterification reaction using methanol and KOH catalyst under sonication. Percentage rendement  of  weight  per  biomass  Nannochloropsis  sp.    is  48,33  %. Characterization of biodiesel was carried out in terms of physical properties: density, viscosity, and chemical properties: FFA content, saponification value, and iodine value. The result showed that analysis characterization biodiesel phytoplankton Nannochloropsis  sp.  that  biodiesel  from  that  species  phytoplankton  generally fullfilled the American Society for Testing and Materials (ASTM D6751) standard, except  density value was 0,8151 g.cm-3,  viscosity value was 1,15 cSt, and FFA content was 0,5381 %, to be used as fuel.